Directions for Reform : A Country Economic Memorandum for Recovery and Resilience in South Sudan - World Bank (Washington, DC: World Bank, 2022)
South Sudan is at a crossroads in its recovery, reconstruction, and development. Having gained independence in 2011 after two protracted civil wars, the country twice relapsed into conflict: first in 2013 and again in 2016. While the economy began to recover following the 2018 peace deal, progress has stalled amidst a multitude of crises – including the COVID-19 pandemic, climate shocks, and dwindling oil production. At the same time, the broad-based rise in commodity prices due to the war in Ukraine have on balance affected South Sudan adversely. A decade after independence, South Sudan remains caught in a web of fragility and economic stagnation, with weak institutions, recurring cycles of violence, and ubiquitous poverty. Overall, the conflict is estimated to have cost South Sudan an accumulated loss in aggregate GDP of some US$81 billion during 2012 – 2018, equivalent to $11.6 billion per year on average (80 percent of 2010 GDP). Consequently, South Sudan’s real GDP per capita in 2018 was estimated at being one third of the counterfactual estimated for a non-conflict scenario. With the fragile peace deal largely holding despite challenges in implementation, the authorities initiated an ambitious reform program aimed at macroeconomic stabilization and modernization of the young country’s public financial management systems. This report discusses South Sudan’s economic performance since independence, with a focus on leveraging the country’s endowments of natural capital – oil and arable land – to support recovery and resilience. Three messages emerge from this report. First, there is a peace dividend in South Sudan. South Sudan’s real GDP per capita in 2018 was estimated at one third of the counterfactual estimated for a non-conflict scenario. Thus, maintaining peace can by itself be a strong driver of growth. Second, with better governance and accountability, South Sudan’s oil resources can drive transformation. Third, South Sudan’s chronic food insecurity could be reversed with targeted investments to improve the resilience of the agricultural sector.